2000
DOI: 10.1182/blood.v96.12.3907.h8003907_3907_3914
|View full text |Cite
|
Sign up to set email alerts
|

Flt3 mutations from patients with acute myeloid leukemia induce transformation of 32D cells mediated by the Ras and STAT5 pathways

Abstract: Somatic mutations of the receptor tyrosine kinase Flt3 consisting of internal tandem duplications (ITD) occur in 20% of patients with acute myeloid leukemia. They are associated with a poor prognosis of the disease. In this study, we characterized the oncogenic potential and signaling properties of Flt3 mutations. We constructed chimeric molecules that consisted of the murine Flt3 backbone and a 510-base pair human Flt3 fragment, which contained either 4 different ITD mutants or the wild-type coding sequence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…Aberrant stimulation of proteins that confer a proliferative advantage was first identified in mutant-FLT3 myeloid leukemia cells. In vitro, the 32D mouse myeloid cell line harboring the ITD-mutation showed factor-independent proliferation and resistance to radiation-induced apoptosis [73,74]. Both STAT5 and Ras pathways were shown to be activated.…”
Section: Flt3 Mutant Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant stimulation of proteins that confer a proliferative advantage was first identified in mutant-FLT3 myeloid leukemia cells. In vitro, the 32D mouse myeloid cell line harboring the ITD-mutation showed factor-independent proliferation and resistance to radiation-induced apoptosis [73,74]. Both STAT5 and Ras pathways were shown to be activated.…”
Section: Flt3 Mutant Signalingmentioning
confidence: 99%
“…Constitutively phosphorylated STAT5 has been observed in primary AML blasts and in immortalized cell lines Ba/F3 and 32D that express the mutated FLT3 receptor [64,73,74,78,79]. The phosphorylation of STAT5 contrasts most clearly with the wild-type signaling pathway because normal FL-activated of FLT3 does not cause significant STAT5 activation.…”
Section: Flt3 Mutant Signalingmentioning
confidence: 99%
“…These mainly occur in the activation loop of FLT3, mostly representing point mutations in codon D835 or, less frequently deletions of codon I836 (84). Only approximately 1% carry the in AML dominating FLT3 ITD that is result of a duplication of a stretch of several amino acids in the juxtamembrane region of the receptor and facilitate leukemic transformation by inducing constitutive kinase activation and signaling through the Ras and JAK/STAT5 pathways (92).…”
Section: Oncogenic Activation Of Non-b Lymphoid Cytokine Receptorsmentioning
confidence: 99%
“…Raf/MAP kinase pathways are induced by the ligand-activated wild type, where STAT5 pathway is induced particularly by mutated FLT3. STAT5 activates proliferative and antiapoptotic pathways, which are considered to play an essential role in FLT3-ITD-positive AML pathogenesis (29,30). Vempati et al (31) suggested that tyrosine residues in positions 589 and 591 are important for STAT5 phosphorylation, whereas tyrosine residues in positions 597 and 599 are necessary for the structural maintenance of FLT3-ITD for STAT5 recruitment.…”
Section: Discussionmentioning
confidence: 99%